Comparison of open reduction and internal fixation and radial head resection for treatment of Mason type 2 and 3 fractures in young and active patients: our experience - Ferrara, Massimo; Sangaletti, Rudy; Reina, Micaela; Niccoli, Giuseppe; Benazzo, Francesco; Terragnoli, Flavio (Lo Scalpello - Journal, 2022)
Objective. The management of Mason type II and III radial head fractures (RHF) is still a debated topic. In the past, the only treatment of choice was radial head resection (RHR) but, as surgical techniques and instrumentation have advanced, internal screw fixation (ORIF) has gained popularity. The aim of this paper is to compare in a retrospective analysis the outcomes of ORIF and RHR in these fracture patterns in young patients. Methods. A total of 37 patients (age between 20 and 60 years old) affected by Mason type 2 and 3 RHF and surgically treated were collected by means of our electronic hospital database. Sixteen patients underwent RHR, and 21 patients underwent ORIF with mini screws. Functional outcomes and scores as well as the radiographs were recorded during follow-up. Results. After 22.17 months (range 12-45) of mean follow-up, the mean DASH, UCLA and MEPS scores showed no significant differences between groups (p: 0.26; 0.21; 0.23). The VAS score was unfavorable in the ORIF group compared to the RHR group (p: 0.43) although not statistically significant. Conclusions. The gold standard in the management of these fractures is not universally recognized. The advantages and complications of both techniques as well as of the RH arthroplasty are abundantly described. Our outcomes support RHR as a possible treatment choice in multi-fragmentary fractures of RH in young patients while minimizing complications.